Fibrous bimetallic silver palladium and ruthenium palladium nanocrystals exhibit an exceptionally high active catalytic process in acetone hydrogenation. (December 2019) - Mawarnis, E.R.; Umar, A.A.
Abstract: Highly dynamic catalytic reaction requires synergetic process of active adsorption and desorption of reactants on the catalyst's surface. This can be measured from the product yield and the catalyst's lifetime during the catalysis process. In this study, we discovered that bimetallization of the well-known Pd catalyst with Ag or Ru atoms modifies its crystal growth orientation and catalytic properties, leading to the generation of large area (due to fibrous structure) and unusual surface physicochemical properties for a highly energetic catalytic reaction in a model of a catalytic reaction, that is, acetone hydrogenation to produce isopropanol. In typical process, the kinetic rate of the reaction can be up to as high as 5.5 × 10 −2 and 6 × 10 −3 for AgPd and RuPd nanocatalysts, respectively, which are equivalent to the turnover frequency as high as of 2.3 × 10 2 s −1 and 1.4 × 10 2 s −1 for AgPd and RuPd nanocatalysts, respectively. This performance is much higher than the pristine Pd nanocatalyst and other nanocatalysts reported recently. The synthesis and the mechanism of catalytic properties enhancement will be discussed. Graphical abstract: Fibrous AgPd and RuPd nanocatalysts offer highly dynamic and highly efficient catalytic process. AgPd, silver palladium; RuPd, ruthenium palladium. Image 1 Highlights: A simple approach for the synthesis of fibrous bimetallic nanocrystals of silver palladium (AgPd) and ruthenium palladium (RuPd) is demonstrated. Fibrous nanocrystals of AgPd and RuPd exhibit unusually high catalytic performance in acetone hydrogenation reaction. Fibrous bimetallic nanocrystals facilitate highly dynamic surface reaction.